Effect of different anticonvulsants on liver enzyme activities in patients with seizure disorder - Dhungana, Arun; Pandeya, Arun; Shakya, Dipesh; Pokharel, Babu Ram (Journal of Chitwan Medical College, 2022)
Background: Epilepsy is a common chronic neurological disorder characterized by recurrent unprovoked seizures, which has transient signs and/or symptoms of abnormal, synchronous neuronal activity in the brain. Antiepileptic drugs (AEDs) used for the prevention of seizure have been found to be an inducer of liver enzyme activity. So, the purpose of this study was to see the effect of antiepileptic drugs on hepatic enzymes activity. Methods: An observational study was carried out in Kathmandu Medical College from October 2020 to April 2021 at neurology department. Sixty-seven seizure patients aged 19-89 years were included in the study. Liver function test was performed before medication, followed up and monitored for three and six months. Paired sample t-test was used to compare the means by using SPSS version 15. Results: Among carbamazepine (CBZ) and sodium valproate (VPA) treated cases, 4.5% and 9.1% respectively showed raised Alanine aminotransferase (ALT) activity whereas, 13.6% and 4.5% respectively showed raised Alkaline Phosphatase (ALP) activity. ALT activity was higher in VPA treated patient compared to CBZ treated patient. However, ALP activity was raised in CBZ treated patient compared to VPA treated patients. No, change in liver enzyme activities was observed in patient treated with Levetiracetam Conclusions: Anticonvulsant drugs used during the treatment have mild to moderate hepatotoxicity. Liver enzyme activity more than two to three-fold may increase. Levetiracetam has minimal hepatic metabolism while sodium valproate is more hepatotoxic. Therefore, routine screening of hepatic enzymes is recommended to the patients under antiepileptic therapy.